Fundamental limitations in transferred CVD graphene caused by Cu catalyst surface morphology. (15th August 2020) - Huet, Benjamin; Raskin, Jean-Pierre; Snyder, David W.; Redwing, Joan M.
Abstract: The transfer of large-area graphene is a critical step in the development of technological applications, particularly when its structural integrity and physical properties are of central importance. While the scientific community dedicated a great deal of efforts improving the scalability and cleanliness of the transfer protocol, less research focused on the fundamental mechanisms responsible for the formation of cracks, wrinkles, corrugations, folds and mechanical strain which drastically hinder the reliability of the process. Here we describe how the surface morphology of copper, which serves as catalyst for the graphene chemical vapor deposition (CVD), significantly impacts (i) the transfer process reliability, (ii) graphene's planar aspect, and (iii) graphene's physical properties once transferred onto device-compatible substrates. We systematically compare the transfer of highly crystalline graphene from Cu foils, polycrystalline Cu films and epitaxial Cu films which possess a surface roughness spanning over 2 orders of magnitude. Our results suggest that, regardless of the transfer approach, the Cu template surface morphology is one of the major causes for the non optimal transfer results and discrepancies in physical properties reported in the literature. These findings provide valuable insights encouraging the use of alternative substrates when considering the integration of graphene into functional applications. Graphical abstract: Image 1